Sistema colinérgico e peroxidação lipídica de ratos tratados com sulfato de vincristina e decanoato de nandrolona - Martins, Danieli Brolo (2008)
Vincristine sulphate is antitumor agent widely used in small animal clinical oncology; therefore it can cause a number of adverse effects including marrow and neuronal cytotoxicity. Nandrolone decanoate, an anabolic-androgenic steroid (AAS), has been used in association with vincristine in order to ease effects such as moderate myelosuppression. The present dissertation presents data related to the isolated or associated employment of vincristine sulphate and nandrolone decanoate, as well as their effects on the cholinergic system and oxidative profile of Wistar rats. The animals were submitted to four different doses of AAS for three weeks and its action on acetylcholinesterase (AChE) activity in four different structures of brain tissue (cerebellum, hippocampus, striatum and cerebral cortex) was studied. The second experiment shows the effects of vincristine and/or nandrolone decanoate in the brain (same parts studied previously) and blood through measurement of brain and red blood cell AChE (RBC-AChE) enzyme activity as well as brain and blood serum lipid peroxidation of rats treated for two weeks. Results show that the two highest doses used in the first experiment increased enzyme activity, suggesting interference in the cholinergical system of the striatum and cerebellum. The results obtained in the latter experiment demonstrate that the isolated use of this AAS and its association with vincristine sulphate altered brain and RBC-AChE action, both in a stimulatory and inhibitory fashion. Lipid peroxidation, in the brain and blood, increased due to the isolated use of both vincristine and nandrolone decanoate, as well as to their associated use at the highest dose of ester used. Furthermore, the data show that the association between the therapeutic dose of nandrolone decanoate and vincristine is capable of neutralizing the free radical production induced by their isolated use in brain and blood serum. Serum RBC-AChE activity and the oxidative profile presented in this study are similar to those exhibited for brain tissue. Based on these data, it can be concluded that nandrolone decanoate is capable of interfering in AChE activity, affecting the cholinergic system, which could cause an alteration of its neurotransmitter, as well as a low or high stimulation of post-synaptic receptors. Therefore, the use of the therapeutic dose of AAS studied here in association with vincristine has been shown to be beneficial, as it could protect the organism from damaging processes caused by the production of free radicals.